Failure Pattern Transition of Shape Memory NiTi Foam Subjected to Compression: From Quasi-Static to Dynamic - Xiaojuan Wang; Hongyuan Zhou (Applied Sciences, 2018)
Shape memory alloy can recover its original configuration, while lightweight foam can absorb a considerable amount of energy. It is desirable to test whether shape memory foam has merits in terms of both shape memory effect and exceptional energy absorption capacity. In the present study, shape memory NiTi foam is compressed quasi-statically and dynamically in order to investigate its response and failure pattern transition with an increasing loading rate. A universal testing machine is used in a quasi-static test, while the split Hopkinson pressure bar is employed in the dynamic test. It is observed that the NiTi foam fails differently: under a quasi-static load, small foam parts of various sizes fall off from the specimen fringe; meanwhile, under dynamic load, the foam fractures in the specimen center to split it into multiple pieces. The underlying failure mechanisms accounting for the shape memory foam behavior under different loading rates are discussed.